Understanding ethical challenges of family planning interventions in sub–Saharan Africa: a scoping review - Montt-Maray, Eloisa; Adamjee, Lamiah; Horanieh, Nour; Witt, Alice; González-Capella, Thaïs; Zinke-Allmang, Anja; Cislaghi, Beniamino (Frontiers in Global Women's Health, 2023)
Background Improving the design of family planning (FP) interventions is essential to advancing gender equality, maternal health outcomes, and reproductive autonomy for both men and women. While progress has been made towards applying a rights-based approach to FP interventions in sub-Saharan Africa, the ethical implications of FP interventions has been underreported and underexplored. Several ethical challenges persist related to measuring success, choice, and target population. Methods We conducted a scoping review to understand if and how FP interventions published between 2000 and 2020 within sub-Saharan Africa address the ethical challenges raised within the literature. We identified a total of 1,652 papers, of which 40 were included in the review. Results Our review demonstrated that the majority of family planning interventions in sub-Saharan Africa place a strong emphasis, on measuring success through quantitative indicators such as uptake of modern contraception methods among women, specifically those that are married and visiting healthcare centres. They also tend to bias the provision of family planning by promoting long-acting reversible contraception over other forms of contraception methods potentially undermining individuals' autonomy and choice. The interventions in our review also found most interventions exclusively target women, not recognising the importance of gender norms and social networks on women's choice in using contraception and the need for more equitable FP services. Conclusion The results of this review highlight how FP interventions measured success through quantitative indicators that focus on uptake of modern contraception methods among women. Utilising these measures makes it difficult to break away from the legacy of FP as a tool for population control as they limit the ability to incorporate autonomy, choice, and rights. Our results are meant to encourage members of the global family planning community to think critically about the ethical implications of their existing interventions and how they may be improved. More public health and policy research is required to assess the effect of applying the new indicators with the FP community as well as explicitly outlining monitoring and evaluation strategies for new interventions to allow for programme improvement and the dissemination of lessons learned.